Projections in operator ranges - Corach, Gustavo (2006)
If H is a Hilbert space, A is a positive bounded linear operator on H and S is a closed subspace of H, the relative position between S and A-1 (S⊥) establishes a notion of compatibility. We show that the compatibility of (A, S) is equivalent to the existence of a convenient orthogonal projection in the operator range R(A1/2) with its canonical Hilbertian structure.